Wealth and poverty: lessons from economic history - Rajwade, A.V. (2000)
Non-economic factors have as much, if not more, to do with the wealth and poverty of nations as endlesly argued fiscal deficits and interest rates. Do the cultural value systems of people and organisations foster learning, innovation, enterprise and debate? While on the subject, when did we last hear of a major Indian politician or policy-maker saying that we need to learn - say, about microcredit from Bangladesh? - Reproduced
Keywords: Economic history; Poverty